Hepatic Transcriptome Analysis Identifies Divergent Pathogen-Specific Targeting-Strategies to Modulate the Innate Immune System in Response to Intramammary Infection - Heimes, Annika; Brodhagen, Johanna; Weikard, Rosemarie; Seyfert, Hans-Martin; Becker, Doreen; Meyerholz, Marie M.; Petzl, Wolfram; Zerbe, Holm; Hoedemaker, Martina; Rohmeier, Laura; Schuberth, Hans-Joachim; Schmicke, Marion; et al. (Frontiers in Immunology, 2020)
Mastitis is one of the major risks for public health and animal welfare in the dairy industry. Two of the most important pathogens to cause mastitis in dairy cattle are Staphylococcus aureus (S. aureus) and Escherichia coli (E. coli). While S. aureus generally induces a chronic and subclinical mastitis, E. coli is an important etiological pathogen resulting in an acute and clinical mastitis. The liver plays a central role in both, the metabolic and inflammatory physiology of the dairy cow, which is particularly challenged in the early lactation due to high metabolic and immunological demands. In the current study, we challenged the mammary glands of Holstein cows with S. aureus or E. coli, respectively, mimicking an early lactation infection. We compared the animals’ liver transcriptomes with those of untreated controls to investigate the hepatic response of the individuals. Both, S. aureus and E. coli elicited systemic effects on the host after intramammary challenge and seemed to use pathogen-specific targeting strategies to bypass the innate immune system. The most striking result of our study is that we demonstrate for the first time that S. aureus intramammary challenge causes an immune response beyond the original local site of the mastitis. We found that in the peripheral liver tissue defined biological pathways are switched on in a coordinated manner to balance the immune response in the entire organism. TGFB1 signaling plays a crucial role in this context. Important pathways involving actin and integrin, key components of the cytoskeleton, were downregulated in the liver of S. aureus infected cows. In the hepatic transcriptome of E. coli infected cows, important components of the complement system were significantly lower expressed compared to the control cows. Notably, while S. aureus inhibits the cell signaling by Rho GTPases in the liver, E. coli switches the complement system off. Also, metabolic hepatic pathways (e.g. lipid metabolism) are affected after mammary gland challenge, demonstrating that the liver restricts metabolic tasks in favor of the predominant immune response after infection. Our results provide new insights for the infection-induced modifications of the dairy cow’s hepatic transcriptome following mastitis.